Genetic and Functional Analyses of PptA, a Phospho-Form Transferase Targeting Type IV Pili in Neisseria gonorrhoeae - Næssan, Cecilia L. (American Society for Microbiology (ASM), 2008)
The PilE pilin subunit protein of Neisseria gonorrhoeae undergoes unique covalent modifications with phosphoethanolamine (PE) and phosphocholine (PC). The pilin phospho-form transferase A (PptA) protein, required for these modifications, shows sequence relatedness with and architectural similarities to lipopolysaccharide PE transferases. Here, we used regulated expression and mutagenesis as means to better define the relationships between PptA structure and function, as well as to probe the mechanisms by which other factors impact the system. We show here that pptA expression is coupled at the level of transcription to its distal gene, murF, in a division/cell wall gene operon and that PptA can act in a dose-dependent fashion in PilE phospho-form modification. Molecular modeling and site-directed mutagenesis provided the first direct evidence that PptA is a member of the alkaline phosphatase superfamily of metalloenzymes with similar metal-binding sites and conserved structural folds. Through phylogenetic analyses and sequence alignments, these conclusions were extended to include the lipopolysaccharide PE transferases, including members of the disparate Lpt6 subfamily, and the MdoB family of phosphoglycerol transferases. Each of these enzymes thus likely acts as a phospholipid head group transferase whose catalytic mechanism involves a trans-esterification step generating a protein-phospho-form ester intermediate. Coexpression of PptA with PilE in Pseudomonas aeruginosa resulted in high levels of PE modification but was not sufficient for PC modification. This and other findings show that PptA-associated PC modification is governed by as-yet-undefined ancillary factors unique to N. gonorrhoeae.